Konsep T}ghut dalam Perspektif Nasir Makarim Shirazi - Sutrisno Hidayatulloh; Ikhlas Budiman (At-Tafasir: Journal of Al-Qur'an Studies and Contextual Tafsir, 2024)
Behaviors such as associating partners with Allah Swt, acting excessively, violating the truth, and not following the laws established by Allah Swt are considered Taghut. Even though they claim to believe in Allah Swt and His Messenger, their actions and attitudes actually seek decisions from Taghut. Some points related to the forms of taghut can be summarized as follows: 1) Satan, 2) Idol Worship, 3) Ka’ab bin al-Asyraf, and 4) rulers who enforce laws that contradict the laws of Allah. Makarim Shirazi also pays a lot of attention to human beings. This is evident as he elaborates in his book Al-Amthal Fī Tafsīr Kitāb Allāh al-Munzal, which in this case serves as a primary data source. Meanwhile, secondary data sources are obtained from various other literatures. This research uses a descriptive-analytical method and a thematic method (mawdu’i), because it not only aims to describe and analyze various issues and data but also focuses more on the discussion theme. Based on Makarim Shirazi's interpretation, he states that every era has its problems and obstacles that arise due to social and civilizational changes. Therefore, it is very important to increase faith and obedience to believe in Allah SWT, the Creator of the universe. Worship Allah alone and avoid taghut